PENGEMBANGAN BAHAN AJAR REFUTATION TEXT UNTUK MEREDUKSI MISKONSEPSI ASAM BASA - Kurnawati, Siska; Enawaty, Eny; Sartika, Rody Putra (Universitas Tanjungpura, 2022)
abstrakThis research was based on the problem of the students misconceptions on the acid-base material. To overcome this misconception, refutation text teaching materials were developed. This study aimed to produce a teaching material and examine the responses of students and teachers at SMA Negeri 6 Pontianak and SMA Negeri 9 Pontianak on teaching materials developed using the ADDIE development model. In a small group trial, the model was applied on 8 students of class XI MIA. In a large group trial, it was applied on 64 students and 2 chemistry teachers in the studied schools. The instrumentation of the research data used were eligibility options, student questionnaires, and teacher response questionnaires. The results of data processing showed that the teaching materials developed are suitable for use in learning from the validation of the feasibility of the material by 92.72%, the feasibility of language by 92.11%, and the feasibility of graphics by 95.89% with a very feasible category. Based on the results of student questionnaire calculations, the responses obtained were 95.31% in small group trials, 89.18% in large group trials, and 91.66% in teacher responses. This showed that the response of students and teachers to refutation text teaching materials for acid-base materials at SMA Negeri 6 Pontianak and MSA Negeri 9 Pontianak was classified as very high. Thus, refutation text can be used as teaching material for acid-base materials.Keywords ADDIE, Misconceptions, Refutation Text